Manifesto for Comprehensive Neo-Schumpeterian Economics - Horst Hanusch; Andreas Pyka (Universität Augsburg, Institut für Volkswirtschaftslehre, 2006)
Within the last 25 years large progress has been made in Neo-Schumpeterian Economics, this branch of economic science which deals with dynamic processes causing qualitative transformation of economies basically driven by the introduction of novelties. By its very nature, technological innovation is the most exponent and visible form of novelty. However, Neo-Schumpeterian Economics should be concerned with all facets of open and uncertain developments. A Comprehensive Neo-Schumpeterian approach has to consider not only transformation processes going on on the industry level of an economy, but also those on the public and monetary realms. Our manifesto introduces these extensions and complements towards a Comprehensive Neo-Schumpeterian economic theory, and develops some guideposts in the sense of a roadmap for necessary strands of analysis in the future.
urn:nbn:de:bvb:384-opus4-711474
Keywords: B52; G10; P0; L2; O40; O30; 330; Neo-Schumpeterian economics; industrial dynamics; public finance; financial markets